Loan moratorium announcements and stock market reaction : an event study analysis - Edie Johari, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Loan moratoriums have been a crucial lifeline defence for many borrowers during the unprecedented COVID-19 pandemic. Despite the massive amount of funds allocated to support affected borrowers, the impact on banks remains unexplored. This study aims to examine the impact of the loan moratorium announcements on Malaysian banks’ stocks. Utilising an event study methodology, this study shows that bank investors reacted differently to different types of loan moratoriums. Bank investors positively valued moratoriums that did not waive accrued interest and covered a broader group of borrowers. This study suggests that while moratoriums must be given to borrowers during difficult times, the financial interests of banks should also be considered. Hence, loan moratoriums should feature accrued interest payments to ensure the banks’ prospects remain stable from the investors’ perspective